2020
DOI: 10.1093/ijnp/pyaa083
|View full text |Cite
|
Sign up to set email alerts
|

PI3K-Akt Signaling in the Basolateral Amygdala Facilitates Traumatic Stress Enhancements in Fear Memory

Abstract: Background A core symptom of post traumatic stress disorder (PTSD) is persistent fear memory, which can be defined as fear memory that is resistant to updating, inhibition, or extinction. PTSD emerges after traumatic stress exposure, but neurobiological mechanisms via which traumatic stress leads to persistent fear memory are not well defined. Akt signaling within the amygdala (Amy) is enhanced with traumatic stress and phosphatidylinositol kinase 3 (PI3K) activation of Akt within the basolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…All these findings would suggest that these miRNAs are part of a complex transcriptional and post-transcriptional machinery that controls fundamental processes in neurons and, consequently, their dysregulation would contribute to molecular cascades induced by neuropsychological stress. Moreover, enrichment analysis of miR-15a-5p, miR-497a-5p, miR-511-5p, and let-7d-5p network showed that such miRNA circuits could affect multiple cellular and molecular processes associated with PTSD pathogenesis [ 47 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Based on these considerations, the inverse correlation between arousal score and hippocampal expression of miR-15a-5p and miR-511-5p is not surprising, as it suggests the existence of a linear relationship between the behavioral arousal score of mice and miRNA levels in the brain that, in turn, coherently influences BDNF and FKBP5 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…All these findings would suggest that these miRNAs are part of a complex transcriptional and post-transcriptional machinery that controls fundamental processes in neurons and, consequently, their dysregulation would contribute to molecular cascades induced by neuropsychological stress. Moreover, enrichment analysis of miR-15a-5p, miR-497a-5p, miR-511-5p, and let-7d-5p network showed that such miRNA circuits could affect multiple cellular and molecular processes associated with PTSD pathogenesis [ 47 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Based on these considerations, the inverse correlation between arousal score and hippocampal expression of miR-15a-5p and miR-511-5p is not surprising, as it suggests the existence of a linear relationship between the behavioral arousal score of mice and miRNA levels in the brain that, in turn, coherently influences BDNF and FKBP5 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…NFkB, for example, is a key transcription factor in stress regulation and stress adaptation [ 40 , 41 ]. Traumatic stress, which may be associated with labor, may enhance PI3-Akt signaling in the basolateral amygdala in the brain, leading to the persistence of fear memory and posttraumatic stress disorder like symptoms [ 42 ]. NFkB and Akt pathways have been implicated in both inflammatory and opioid-induced neuropathic pain pathways [ 43–46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PTSD and impaired glutamate systems cannot maintain adequate glutamate delivery when re-experiencing trauma-related stimuli, leading to increased over-attention, stress response, and fear ( Pitman et al, 2012 ). Activated PI3K/Akt is crucial for the formation of fear memory, and the PI3K/Akt pathway may underlie the anti-regression of fear memory caused by traumatic stress ( Yang et al, 2015 ) and be related to the formation of anxiety-like symptoms in PTSD ( Knox et al, 2021 ). Akt plays an important role in neural development, learning, and memory, and upregulation of the PI3K/Akt pathway may prevent and treat cognitive impairment ( Palumbo et al, 2021 ; Tong et al, 2021 ).…”
Section: Pi3k/akt Pathway In Post-traumatic Stress Disorder Comorbidi...mentioning
confidence: 99%